Interest Rate Transmission on Indonesia’s Monetary Policy Analysis: Case of Banking Interest Rate - Adin Nugroho; Prientananda Ghina Salsabila (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Indonesia's economic stability should be achieved by implementing monetary and fiscal policies, for instance, setting the interest rate by Bank Indonesia (BI) as policy rate of central bank, which should be followed by other banking institutions. Unfortunately, this interest rate regulation by BI had not been able to achieve the goal of restoring economic stability since it always had long time lag. This happened because the policy of increasing interest rates had not been followed up spontaneously by other banking institutions. In fact, time lag might cause disadvantages such as long-lasting high inflation, increased poverty, and severe economy vulnerability. This research was conducted to analyze the time lag of the transmission of Bank Indonesia's interest rate monetary policy and the response of banking institutions in Indonesia. The method used in this study was survival analysis. The results indicated that the time lag of monetary policy transmission using the interest rate in Indonesia needed to be improved to double adjustment speed to reach the optimal point. The response of banking institutions could be improved because there was still asymmetry response in all aspects including types of interest rates, allocations, and change direction. Meanwhile, from the aspect of ownership, both state-owned and private-owned banks had shown in line response of time lag performance.